Intracerebral Hemorrhage-Grading Scale (ICH-GS) Score as a Prognosis Prediction of Spontaneous Intracerebral Hemorrhage at Rumah Sakit Islam Surabaya Jemursari - Aulia, Nurlisa Naila; Syifak, Shobihatus; Yuniati, Dyah; Alam, Ilham Putera; Surya, Prima Ardiansyah (Jurnal Medis Islam Internasional, 2023)
Background: Spontaneous intracerebral hemorrhage or hemorrhagic stroke is one of the leading causes of mortality and disability in Indonesia, but until now there is no specific therapy for this disease. The intracerebral hemorrhage (ICH) score is a widely used predictive tool for the prognosis of death 30 days after spontaneous intracerebral hemorrhage, but the intracerebral hemorrhage-grading scale (ICH-GS) score has a more specific interval to assess the prediction of the prognosis after intracerebral hemorrhage. Rumah Sakit Islam (RSI) Jemursari Surabaya has not carried out data collection related to the ICH-GS score with the outcome (death) of patients with spontaneous intracerebral hemorrhage, especially while still receiving hospital treatment. Objective: To identify the number of ICH-GS scores in patients with spontaneous intracerebral hemorrhage as a predictor of prognosis at RSI Jemursari Surabaya. Method: The type of this research is retrospective research. The population comprised of all patients with spontaneous intracerebral hemorrhage hospitalized at RSI Jemursari Surabaya in 2017-2019, with affordable population of all patients with spontaneous intracerebral hemorrhage diagnosed by a neurologist. Results: The data showed that 5.5% (6 people) had an ICH-GS score of 5; 38.2% (42 people) had an ICG-GS score of 6; 21.8% (24 people) had an ICH-GS score of 7; 20 % (22 people) had an ICH-GS score of 8; 5.5% (6 people) had an ICH-GS score of 9; 4.5% (5 people) had an ICH-GS score of 10; 3.6% (4 people) had an ICH-GS score of 11; and 0.9% (1 patient) had an ICH-GS score of 12. Conclusions: The results of the ICH-GS score can be used to facilitate communication both with fellow health workers and with the patient's family. Trend of the data showed that ICH-GS score is not consistent in showing the prognosis of spontaneous intracerebral hemorrhage (the smaller the ICH-GS score should have better prognosis than the higher score), while the information based only on volume and location can predict the prognosis more consistently`.